Setting of import tolerances for fluxapyroxad in certain root crops and coffee beans. (21st January 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant BASF SE submitted a request to the competent national authority in the United Kingdom to set import tolerances for the active substance fluxapyroxad for certain root crops and for coffee beans produced in the US and Brazil. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals for the crops assessed. Adequate analytical methods for enforcement are available to control the residues of fluxapyroxad in the products concerned at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of fluxapyroxad according to the reported agricultural practices is unlikely to present a risk to consumer health.